Does TPACK Mastery Affect Teamwork Skills? A Causal-Comparative Study of Pre-Service Physics Teachers - Guntara, Yudi; Hafid, Tubagus; Sari, Indah Fatika (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2021)
Physics teachers need to mastery TPACK and teamwork skills because they were essential in work. The purpose of this study was to determine the relationship between TPACK mastery and teamwork skills. The research method used a causal-comparative. The sampling technique used was purposive sampling. The sample consisted of 33 preservice physics teachers from Universitas Sultan Ageng Tirtayasa and Universitas Mulawarman. The data collection method used a questionnaire and an instrument in the form of a questionnaire with a Likert scale in a web-based survey. This instrument is used to measure TPACK and teamwork skills. Data analysis techniques used Pearson's correlation and regression analysis. The results showed no significant relationship between mastery of TPACK and teamwork skills, as indicated by Pearson’s correlation value of 0.061 with a significance of 0.735. However, if further tested based on every aspect of the two variables, there is a significant correlation between technology knowledge (TK), technology content knowledge (TCK) on the mastery of TPACK, and communication aspects on teamwork skills. Based on the regression test, the result obtained more than 90%, the communication aspect of teamwork skills influenced by TK and TCK. Another finding is that the most dominant external factor that influences teamwork skills is gender